Influence of omega-3 PUFAs on the metabolism of proanthocyanidins in rats. (July 2017) - Molinar-Toribio, Eunice; Ramos-Romero, Sara; Fuguet, Elisabet; Taltavull, Núria; Méndez, Lucía; Romeu, Marta; Medina, Isabel; Torres, Josep Lluís; Pérez-Jiménez, Jara
Abstract: Studies of the bioavailability of proanthocyanidins usually consider them independently of other dietary constituents, while there is a tendency in the field of functional foods towards the combination of different bioactive compounds in a single product. This study examined the long-term effects of ω-3 polyunsaturated fatty acids of marine origin on the metabolic fate of grape proanthocyanidins. For this, female adult Wistar-Kyoto rats were fed (18 weeks) with a standard diet supplemented or not with eicosapentaenoic acid/docosahexaenoic acid (1:1, 16.6 g/kg feed), proanthocyanidin-rich grape seed extract (0.8 g/kg feed) or both. A total of 39 microbial-derived metabolites and 16 conjugated metabolites were detected by HPLC-MS/MS either in urine or in the aqueous fraction of feces. An unexpected significant increase in many proanthocyanidin metabolites in urine and feces was observed in the group supplemented with ω-3 polyunsaturated fatty acids group as compared to the animals fed a standard diet, which contains a small amount of polyphenols. However, proanthocyanidin metabolites in rats given ω-3 polyunsaturated fatty acids and grape seed extract did not significantly differ from those in the group supplemented only with grape seed extract. It was concluded that ω-3 polyunsaturated fatty acids collaborate in the metabolism of polyphenols when present at low doses in the feed matrix, while the capacity of ω-3 polyunsaturated fatty acids to induce microbiota transformations when proanthocyanidins are present at high doses is not relevant compared to that of polyphenols themselves. Graphical abstract: Highlights: ω-3 PUFAs influence the metabolism of proanthocyanidins (PAs). ω-3 PUFAs increase metabolites of PAs present in the standard diet. ω-3 PUFAs do not increase PA metabolites when PA are given as a supplement. ω-3 PUFAs do not significantly affect PA metabolism given at high doses.